2021
DOI: 10.1002/er.7009
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology to estimate future water‐energy nexus based on artificial neural networks

Abstract: Summary We propose a new methodology to evaluate future electricity generation scenarios aiming to explore implications of different sets of power plants on the water‐energy nexus (W‐EN). We use two artificial neural networks: cascade forward back propagation and Kohonen neural networks (KNN). Initially, the future electricity production of the area under investigation is determined. Sequentially, water consumption is calculated for different combinations of plants. The scenarios with the lowest annual water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…This could lead to water consumption constraints that force to reduce the water use in power plants. Carvalho and Carneiro [14] evaluated future electricity generation scenarios to study the effects of different sets of power plants on the water-energy nexus, and they concluded that CSP plants with wet or hybrid cooling systems would represent 92% of the water consumption by 2050 for the scenario where the 100% of the electricity is produced by renewable energies (combining solar and wind plants). Therefore, dry cooling should be considered as an alternative to wet cooling for CSP plants to reduce the water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to water consumption constraints that force to reduce the water use in power plants. Carvalho and Carneiro [14] evaluated future electricity generation scenarios to study the effects of different sets of power plants on the water-energy nexus, and they concluded that CSP plants with wet or hybrid cooling systems would represent 92% of the water consumption by 2050 for the scenario where the 100% of the electricity is produced by renewable energies (combining solar and wind plants). Therefore, dry cooling should be considered as an alternative to wet cooling for CSP plants to reduce the water consumption.…”
Section: Introductionmentioning
confidence: 99%